Zilmax alters blood constituents of finishing cattle - C.L. Van Bibber; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2012)
The purpose of this experiment was to determine the effects of Zilmax (Merck Animal Health, Summit, NJ) on changes in blood metabolites. Zilmax is a feed additive designed to improve production efficiency in cattle when fed during the last phase at the feedlot. Zilmax works by redirecting the energy use in the body to form more lean muscle at the expense of fat deposition. The blood metabolites measured in our experiment were glucose and lactate, which are the energy sources for various body functions including muscle growth. Plasma urea nitrogen was measured as an indicator of protein catabolism. Non-esterified fatty acids also were measured as they were released into the bloodstream with the breakdown of adipose tissue.
Keywords: Cattlemen& #x27; s Day; 2012; Kansas Agricultural Experiment Station contribution; no. 12-231-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1065; Beef Cattle Research; 2012 is known as Cattlemen& #x27; s Day; Beef; Zilmax; Finishing cattle; Blood